Optimization of Ornithogalum Saundersiae Baker Propagation by Twin Scale Cuttings with the Use of Biopolymers - Salachna Piotr,; Zawadzińska Agnieszka, (Journal of Basic & Applied Sciences, 2014)
Ornithogalum saundersiae Baker, commonly known as Giant Chincherinchee, is an interesting bulbous plant with horticultural and medicinal potential. For increasing production of O. saundersiae planting material can be used rapid propagation by twin scaling. The aim of the study was to investigate the effect of parent bulb circumference, twin scale cutting weight and the type of biopolymer coating on the yield of O. saundersiae bulblets. Propagules were encapsulated in three polymer mixtures: 1% gellan and 0.5% chitosan; 1% iota-carrageenan and 0.5% chitosan; 1% xanthan and 0.5% chitosan. Chitosan had a molecular weight (Mw) of 48 000 g·mol-1 and degree of deacetylation (DD) 85%. The twin scale cuttings were mixed with perlite and peat 1:1 (v/v) and stored for 100 days at 22-24˚C and relative humidity of 70-80%. The highest number of bulblets was produced by the parent bulbs 22-24 cm in circumference. The bulblets derived from the twin scale cuttings weighing 2.1-4.1 g were characterized by greater fresh weight, the greatest circumference and they produced the highest number of adventitious roots. Encapsulation of twin scale cuttings in gellan and chitosan or in iota-carrageenan and chitosan, resulted in the bulblets with more roots and greater weight and circumference, as compared to the control ones and the bulblets obtained from scales treated with xanthan and chitosan.